Optimizing the Millennial Role in Communities with Islamic Leadership Training - Muhammad Rizqi Hidayat; Tulaihah Ning Safitri (Universitas Muhammadiyah Mataram, 2019)
The millennial role in society as an agent of change towards the character of the present age youth who are indifferent to their surroundings as expected by the form of optimizing Islamic youth leadership in their environment. This study discusses how important the character of Islamic leadership in the millennium is now. The study population was youth cadets Sidoarum village in Yogyakarta. The purpose of this study was to determine the effect of Islamic leadership training on a millennial character to play a role in society. This type of research is qualitative descriptive with the